2007
DOI: 10.1093/occmed/kqm076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the hand arm vibration syndrome: thermometry, plethysmography and the Stockholm Workshop Scale

Abstract: Background The Stockholm Workshop Scale (SWS) provides a staging scheme for hand-arm vibration syndrome (HAVS) based on subjective history. Cold provocation finger thermometry and plethysmography are commonly used objective tests for the vascular component of HAVS. AimTo examine the correlation between the cold provocation tests and SWS vascular stage. A secondary goal was to evaluate the correlation between cold provocation finger plethysmography and thermometry testing. MethodsPatients investigated for HAVS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The diagnostic value of finger thermometry and PPG in the assessment of HAVS was discussed by Bogadi-Sare and Zavalić [ 24 ]. SWS and PPG scores were weakly correlated, and the authors suggested that they measure two different aspects of the vascular response [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic value of finger thermometry and PPG in the assessment of HAVS was discussed by Bogadi-Sare and Zavalić [ 24 ]. SWS and PPG scores were weakly correlated, and the authors suggested that they measure two different aspects of the vascular response [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cold provocation finger thermometry and plethysmography, such as strain gauge plethysmography and photoplethysmography (PPG), are commonly used laboratory tests for VWF. PPG [ 3–6 ] is a non-invasive optical technique that uses low-intensity light to detect blood volume changes in the microvascular tissue bed [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] In traumatology, impedance plethysmography has been used to assess changes in blood flow following the application of low temperature for extremity injuries. [17,18] In occupational medicine, impedance plethysmography has been used in a number of studies regarding the influence of exposure to topical vibration on the peripheral blood flow in limbs [19][20][21][22]. It has also been used to examine the changes of the peripheral blood flow in response to topical cooling of limbs [23,24].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The cold provocation test is a valuable objective tool for monitoring of vibration induced neurovascular disturbances with dose-effect relation between the cold-provoked vasomotor response and the cumulative vibration exposure. 12 Thermistor thermometry of the limbs, combined with distal Doppler sonography and cold provocation test correlate signifi cantly with each other and with the stage of vibration disease 13 , making their application for objective assessment of autonomic neurovascular injuries in vibration disease appropriate. 14 С. Aström et al determine signifi cant correlation between whole-body vibrations exposure and the increased risk for musculoskeletal alterations in the neck, the shoulders and the wrists similar to those caused by local vibration impact as well as dependence on the cumulative time of exposure.…”
Section: Discussionmentioning
confidence: 99%